International remittances and income inequality: An empirical investigation - Valerie Koechlin; Gianmarco León (Inter-American Development Bank, Research Department, 2006)
The aim of this paper is to provide comprehensive empirical evidence on the relationship between international remittances and income inequality. In simple cross-country regressions we find a non-monotonic link between these two variables when using ordinary least squares, instrumental variables; we also test our hypothesis using dynamic panel data methods. We provide evidence in support of existing theoretical work that accounts for network effects that describe how, in the first stages of migration history, there is an inequality-increasing effect of remittances on income inequality. Then, as the opportunity cost of migrating is lowered due to these effects, remittances sent to those households have a negative impact on inequality. We also show how education and the development of the financial sector can help countries to reach the inequality-decreasing section of the curve more quickly. Our results are robust to several empirical specifications, as well as for a wide variety of inequality measures.
Keywords: O1; O15; J16; 330; Migration; International Remittances; Income distribution